ARCHIVE LAYOUT AND ARCHIVE MANAGEMENT IN THE SUB-DISTRICT OFFICE OF BABAT, LAMONGAN REGENCY: TATA RUANG ARSIP DAN PENGELOLAAN ARSIP DI KANTOR KECAMATAN BABAT, KABUPATEN LAMONGAN - Tiara Kusumaningtiyas; Dyah Puspitasari Srirahayu; Esti Putri Anugrah; Yuni Kurniasari; Michael Fernando Arthur Unso; Rizki Imroatush Shofi; Arik Afif Diaz Musafa; Bagaskara Fatchurahman (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Archives in the Sub-district include various archives from each field as well as report archives from the village. Archives, as valuable organizational assets for institutions, must be managed based on archival science principles by paying attention to the archive storage system and procedures in order to maintain and facilitate archive retrieval. Objective: This study aims to describe the spatial layout and management of archives in the Babat Sub-district Office, Lamongan Regency. Method: Data sources were obtained from oral sources told by informants and direct review of conditions in the Archives Room of the Babat Sub-district Office, Lamongan Regency. In addition, archive arrangement activities were carried out for one month. Results: The results of this study are that archive storage in the Babat Sub-district Office, Lamongan Regency is carried out in a room which is specifically for archive management. However, in the archive layout there are still some inconsistencies with the procedures that can affect the quality of archive storage. Conclusion: in the Babat District Office, archive arrangement and archive management have been carried out, but there are still inconsistencies with the procedures for managing and storing archives.